Converging truths : Euripides' Ion and the Athenian quest for self-definition - Zacharia, Katerina, 1967- (Mnemosyne, Supplements, 2003)
This book is a study of the Ion of Euripides. Produced in a period of intense political crisis at Athens in 412 BC, this play went to the heart of Athenian self-perception but also highlighted the violent divine grace of Apollo, the intense emotional suffering of Kreousa, and Ion's insistent search for truth despite divine concealment. Informed by recent scholarship on Athenian ethnicity, this study shows how autochthony (claim to being earthborn) and Ionianism (Ionian character of Athens) are conceptually related with Apollo, father of Ion and god of the Delphic oracle where the play is set. Through careful analysis of the political, psychological, religious and poetic aspects of the play and use of modern critical theory, the Ion emerges as a polyphonic work expressing different and converging truths.